Draft Regional Plans Ready for Madurai, Nilgiris - (:unkn) unknown (Electronic Media, 2025)
Madurai and Nilgiris regions will soon have regional plans as the Directorate of Town and Country Planning (DTCP) has completed draft plans and submitted them to the State government for its approval before seeking public opinion.
Keywords: Sustainable Development; Regional Planning